Determination of the factor space of the process of extrusion of sausage products - Kuzmin, Oleg; Pasichnyi, Vasyl; Levkun, Kateryna; Riznyk, Anastasiia (My University, 2017)
The aim of the paper is to determination of the factor space of the process of extrusion of sausage products.
Keywords: факторний простір; шприцювання; ковбасні вироби; факторное пространство; колбасные изделия; factor space; extrusion; sausage products; кафедра технології ресторанної і аюрведичної продукції; кафедра технології м’яса і м’ясних продуктів